Answer:
X1 =
and X2 =
![(-15-√(285) )/(6)](https://img.qammunity.org/2022/formulas/mathematics/high-school/s3jhlascc4n6xkmckn8dht1l6hnv5ndynv.png)
Explanation:
To find the roots of a quadratic equation, you need to solve the quadratic equation by using the quadratic formula.
OR
You can use the (Equation/Function) mode on the calculator.
![\frac{-b+-\sqrt{b^(2) -4ac } }{2a} x \\eq 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/o4vvjuqecxalat4jxqgx8g323keiimi9tv.png)
For this equation,
a = 3
b = 15
c = -5
X1 =
![\frac{-15+\sqrt{15^(2) -4(3)(-5) } }{2(3)} x \\eq 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/9x1xhxycwxxoff392g5ux5yt7a2nwv4cpw.png)
X2 =
![\frac{-15-\sqrt{15^(2) -4(3)(-5) } }{2(3)} x \\eq 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/wbkgt71sz5tj3aqpst6pv2ztfcb1ucqh4t.png)
Solving this on the calculator and you should get
X1 =
X2 =
![(=15-√(285) )/(6)](https://img.qammunity.org/2022/formulas/mathematics/high-school/pehdtc9l8hnugwcajfwy7cjwty1aeopebg.png)
a, b, c = constants, where a ≠ 0
x = the unknown